Case Report: Mutation in AIMP2/P38, the Scaffold for the Multi-Trna Synthetase Complex, and Association With Progressive Neurodevelopmental Disorders - Mazaheri, Mahta; Yavari, Mahdie; Zare Marzouni, Hadi; Stufano, Angela; Lovreglio, Piero; D'Amore, Simona; Jahantigh, Hamid Reza (Frontiers in Genetics, 2022)
Background. Leukodystrophies constitute a heterogeneous group of inherited disorders primarily affecting the white matter of the central nervous system. Aminoacyl-tRNA synthetases (ARSs) catalyze the attachment of an amino acids to their cognate transfer RNAs (tRNAs). Pathogenic variants in both cytosolic and mitochondrial ARSs have been linked to a broad range of neurological disorders, including hypomyelinating leukodystrophies and pontocerebellar hypoplasias (PCH). Aminoacyl tRNA synthetase-interacting multifunctional protein 2 (AIMP2), one of the three non-catalytic components, harbors anti-proliferative activity and functions as a proapoptotic factor thus promoting cell death. We report a case of a 7-month-old infant with a complex clinical presentation, including weight loss, severe anemia, skeletal abnormalities, microcephaly and MR imaging features of leukodystrophy with a novel mutation in AIMP2. Methods. Whole-exome sequencing (WES) was performed on the proband. Parental samples were analyzed by PCR amplification and Sanger sequencing. Results. WES revealed a novel variant c.A463T in the homozygous state in exon 3 (NM_001326607) of AIMP2 in the proband. Parental carrier status was confirmed by target sequencing. Conclusion. Here, we present an Iranian case with leukodystrophy with a novel AIMP2 mutation. This finding broadens the mutational and phenotypic spectra of AIMP2-related leukodystrophy and offers guidance for proper genetic counselling for pre- and post-natal screenings as well as for disease management.